2020
DOI: 10.3390/app10175726
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of As, Cd, Cr, Hg, Ni, and Se Concentrations in Organic Amendments Using Portable X-ray Fluorescence and Multivariate Modeling

Abstract: Portable X-ray fluorescence (pXRF) has been a widely used technique in various applications. However, its use for the analysis of organic amendments (composts, sewage sludges, organic fertilizers) is scarce. In these matrices, concentrations of some elements are below their detection limit. The objective of this work was to find multiple linear regression equations that were able to predict the aqua-regia-soluble concentrations of the elements As, Cd, Cr, Hg, Ni, and Se using the pXRF readings of other measura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The basic search in SCOPUS provided 23 records of which only 13 papers [28][29][30][31][32][33][34][35][36][37][38][39][40] deals with organic amendments. The other papers focused on soils or archaeological studies and were discarded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic search in SCOPUS provided 23 records of which only 13 papers [28][29][30][31][32][33][34][35][36][37][38][39][40] deals with organic amendments. The other papers focused on soils or archaeological studies and were discarded.…”
Section: Resultsmentioning
confidence: 99%
“…López et al [33] showed that it was also possible to determine the organic matter content of organic amendment samples from linear regression equations that use the undetermined content data (the difference to 100% of all the elements actually measured) with corrections from elements such as silicon, calcium, or iron. The same authors [36] found multiple linear regression equations that can predict aqua regia-soluble concentrations of the elements As, Cd, Cr, Hg, Ni, and Se using pXRF readings of other measurable elements as predictor variables. These target elements were below the LODs of the pXRF instrument used.…”
Section: Derived Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference material SRM 2709 San Joaquin Soil [ 45 ], recommended for baseline trace element concentrations, produced by the National Institute of Standards and Technology (NIST, Spain), was used to assess the accuracy of the pXRF instrument. The measured value for each target analyte should be within ±20% relative difference (RD) of the true value in order to consider the verification check as acceptable [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in most cases at a household level and small farms, the analysis of the maturity and readiness of the final product is performed by empirical tests based on the compost maker's senses and experience, or lack thereof. Physical characteristics such as texture, smell, or color are the major indicators, rather than laboratory tests, rendering it a challenge to have consistent and accurate results at all times [69]. Consequently, if the compost does not achieve optimal levels of maturity and stability, it could slow down the plant growth process and therefore be considered of inferior quality compared with store-bought compost [70].…”
Section: Maturity and Stabilitymentioning
confidence: 99%